The Experience of Survivors of Firearm Suicide Attempts: A Retrospective Case Series - Jeffrey R. Savarino, MD, MPH; Emily Rubin, MD, JD; Peter T. Masiakos, MD, MS; Rachel McLellan, BA; Myron L. Rolle, MD, MSc; Pranav Nanda, MD; Christopher J. Stapleton, MD; Chana A. Sacks, MD, MPH (Annals of Surgery Open, 2024)
Objective:. We sought to identify people who survived firearm suicide attempts to describe the acute stressors, substance use, and mental health conditions related to the attempt. Background:. Most firearm deaths in the United States are the result of suicide. Because firearm suicide attempts have a case fatality rate of approximately 90%, little is known about the precipitating factors that lead to firearm suicide attempts. Methods:. We conducted a retrospective case series of patients admitted to a large hospital system between 2000 and 2019 who survived intentional, self-inflicted gunshot wounds to the head. Through the electronic medical record, we collected information about acute stressors, substance use, and mental health diagnoses before or at the time of the suicide attempt. Results:. Thirty-four patients were included in the study cohort. Patients were predominantly White (74%) and male (88%), with a mean age of 44 (range, 14–82). Nineteen (56%) patients were acutely intoxicated with alcohol upon hospitalization and 17 (50%) patients had a positive urine drug screen. Acute stressors involving interpersonal relationships (53%), work/school (32%), and legal disputes (18%), among others, were documented in 82% of patients. Most patients (65%) had been diagnosed with depression before their index hospitalization. Most patients were discharged to an acute rehabilitation center (41%) or an inpatient psychiatric facility (41%). Conclusions:. Acute stress and alcohol intoxication were common in this cohort of patients who attempted suicide using firearms. These data offer an ability to learn from the experience of survivors of firearm suicide attempts, a rare population.